2022
DOI: 10.1186/s12891-022-05181-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel bone cement injector augments Chinese osteoporotic lumbar pedicle screw channel: a biomechanical investigation

Abstract: Background The study aimed to (1) create a series of pedicle injectors with different number of holes on the sheath especially for the Chinese elderly patients and (2) further investigate the effects of the injectors on the augmentation of pedicle screw among osteoporotic lumbar pedicle channel. Methods This study used the biomechanical test module of polyurethane (Pacific Research Laboratory Corp, USA) to simulate the mechanical properties of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Unilateral cement screw placement can obtain a better xation effect and has a less biomechanical effect on the vertebral body than bilateral bone cement screw placement. However, the design of hollow pedicle screws in this study was different from that of Xu et al [31]. The tailless design of the screw caused less damage to the surrounding muscles and blood vessels, while Xu's screw with a long tail.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Unilateral cement screw placement can obtain a better xation effect and has a less biomechanical effect on the vertebral body than bilateral bone cement screw placement. However, the design of hollow pedicle screws in this study was different from that of Xu et al [31]. The tailless design of the screw caused less damage to the surrounding muscles and blood vessels, while Xu's screw with a long tail.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, Wang et al[18] also con rmed the excellent short and medium-term therapeutic effect of a novel bone cement screw system combined with vertebroplasty for KD in preventing bone cement displacement. Xu et al [31] demonstrated that the bone cement screw combined with PVP could effectively reduce the relative displacement of the bone cement through nite element analysis. Unilateral cement screw placement can obtain a better xation effect and has a less biomechanical effect on the vertebral body than bilateral bone cement screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…Injectable screws could enable cement injection after screw insertion. They may decrease surgical time and placement error compared with solidly cemented screws because the fenestrated screws are not necessary to be removed before cement application 21 . However, an injectable LMS has not yet been designed, and the potential applications of such screws must be identified.…”
Section: Discussionmentioning
confidence: 99%
“…They may decrease surgical time and placement error compared with solidly cemented screws because the fenestrated screws are not necessary to be removed before cement application. 21 However, an injectable LMS has not yet been designed, and the potential applications of such screws must be identified. Additionally, the relationship between the PMMA distribution pattern and the solid and injectable LMS volume has not been studied yet.…”
Section: Current Research and Existing Problems On Relationship Betwe...mentioning
confidence: 99%
“…This choice was similar to that made by Chen et al . 29 and Fu et al ., 30 who investigated the biomechanical characteristics of reinforced pedicle screws by simulating the vertebral cancellous bone structure using synthetic bone modules. The lower extremity metaphysis performed the same role as synthetic bone modules, but it also simulated bone tissue healing and remodeling.…”
Section: Discussionmentioning
confidence: 99%